Uji Organoleptik dan Tingkat Kesukaan Produk Sereal (Madu, Kurma, Kelor, Susu, Katuk, Alpukat) sebagai Minuman Fungsional untuk Memperlancar ASI - Elvika Fit Ari Shanti; Tri Sunarsih; Endah Puji Astuti; Herwinda Kusuma Rahayu (Universitas Tadulako, 2025)
Breast milk provides numerous benefits; however, many mothers face challenges in providing exclusive breastfeeding, one of which is insufficient milk production. This study aimed to evaluate the organoleptic properties and acceptance level of Mamakesuka cereal as a functional beverage to support breast milk production. The study employed an experimental design using a Completely Randomized Design (CRD). Organoleptic testing and acceptance assessment were conducted with 30 trained panelists. The results showed that formulation L2 was the most preferred. The color most frequently selected was dark brown but still acceptable (70.0%), the taste was described as naturally sweet and savory and well liked (56.7%), the aroma was considered distinctive (56.7%), and the texture was perceived as soft, slightly dense, and crunchy (86.7%). In the acceptance test, formulation L2 was also the most favored, with color rated as “very liked” (70.0%), taste as “liked” (63.3%), aroma as “liked” (53.3%), and texture as “liked” (76.7%). In conclusion, formulation L2 was identified as the best Mamakesuka cereal formulation based on organoleptic evaluation and consumer acceptance, indicating its potential for further development as a locally based functional food product.